Pompeii Pizza? (The Biblical archaeology review, 2023)
Excavations in Ancient Pompeii, which was destroyed in 79 CE by the eruption of nearby Mt. Vesuvius, have revealed a traditional Roman home with a central atrium, kitchen shrine, oven, and beautiful frescoes. Astonishingly, one of the frescoes includes a depiction of something that looks an awful lot like pizza, a cuisine that originated in […]